Model validation for a knowledge and practices survey towards prevention of soil-transmitted helminth infections in rural villages in Indonesia - P. Lee; J. M. Kurscheid; B. Laksono; M. J. Park; A. C. A. Clements; C. Lowe; D. E. Stewart; D. J. Gray (Scientific Reports, 2023)
Abstract The rate of soil-transmitted helminth (STH) infection is estimated to be around 20% in Indonesia. Health promotion and health education are cost-effective strategies to supplement STH prevention and control programs. Existing studies suggest that quantitative tools for knowledge, attitudes and practices (KAP) are important to monitor effective community-based STH interventions. However, evidence is limited regarding the applicability of such tools. This study aims to identify the socio-demographic predictors for STH-related knowledge and practices and validate the quantitative tools in population use. A cross-sectional study design was conducted among residents of 16 villages in Central Java, Indonesia. Adult and child respondents were interviewed to assess general knowledge and practices in relation to STH. Two mixed effects models identified the significant factors in predicting knowledge and practice scores. The model predicted knowledge and practice scores were compared with the observed scores to validate the quantitative measurements developed in this study. Participants’ socio-demographic variables were significant in predicting an individual’s STH-related knowledge level and their hand washing and hygiene practices, taking into account household-level variability. Model validation results confirmed that the quantitative measurement tools were suitable for assessing STH associated knowledge and behaviour. The questionnaire developed in this study can be used to support school- and community-based health education interventions to maximize the effect of STH prevention and control programs.